A taxonomic review of the genus Antepipona de Saussure, 1855 (Hymenoptera: Vespidae: Eumeninae) from India - Kumar, Girish P.; Carpenter, James M.; Sureshan, Pavittu M. (Zootaxa, 2016)
A review of 20 Indian species of the genus Antepipona de Saussure with a key to species and subspecies is provided. A new synonymy is proposed for Antepipona biguttata (Fabricius, 1787) =A. excelsa keralensis Lambert, 2004, syn. nov. The parasitic association of Strepsiptera is reported for the first time in the genus Antepipona. Antepipona rufescens (Smith, 1857) is newly recorded from India and A. ovalis (de Saussure, 1853) from Bangladesh. The reported distributions of ten species within India are enlarged.